Marketing's 4 Ps - Jennings, Judy; McCarthy, Kari; Schrank, Jeffrey; Fagerland, Kirk; Learning Seed Company (Chicago, Ill. : Learning Seed, 2009)
Students learn the traditional four Ps of marketing strategy -- product, place, price and promotion; and more importantly, how a focus consumer is at the core of them all, or should be
Title from title screen
The teaching guide for this program is available at www.learning seed.com
Editor, Bill Killian
DVD Format
With English subtitle
Keywords: Marketing; Consumer behavior